1984
DOI: 10.1002/ajim.4700060605
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and progression of pneumoconiosis over nine years in U.S. coal miners: II. Relationship with dust exposure and other potential causative factors

Abstract: Examination of the incidence and progression of pneumoconiosis over 9 years in 1,261 nationally distributed U.S. coal miners has been undertaken in relationship to potential causative factors. Use has been made of a large body of data on dust levels collected by the Mine Safety and Health Administration principally for compliance purposes. Reported dust levels were low and generally under the current 2 mg/m3 standard. No link between dust level and disease progression could be detected. Some evidence was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Ca 2+ is present in all coals, though the Utah coals have highest levels of Ca 2+ released. Epidemiological studies showed that CWP is frequent in Pennsylvania coal workers (Attfield et al, 1984;Attfield & Althouse, 1992;Morgan et al, 1973). In contrast, coals from Utah, with low prevalence of CWP, had little acid soluble Fe 2+ and Fe 3+ .…”
Section: Acid Solubilization Of Iron In Coalsmentioning
confidence: 78%
“…Ca 2+ is present in all coals, though the Utah coals have highest levels of Ca 2+ released. Epidemiological studies showed that CWP is frequent in Pennsylvania coal workers (Attfield et al, 1984;Attfield & Althouse, 1992;Morgan et al, 1973). In contrast, coals from Utah, with low prevalence of CWP, had little acid soluble Fe 2+ and Fe 3+ .…”
Section: Acid Solubilization Of Iron In Coalsmentioning
confidence: 78%
“…Ca 2+ is present in all coals, though the Utah coals have highest levels of Ca 2+ released. Epidemiological studies have shown that CWP is frequent in Pennsylvania coal workers (Morgan et al 1973;Attfi eld et al 1984; Attfi eld and Althouse 1992). In contrast, coals from Utah with low prevalence of CWP had little acid soluble Fe 2+ and Fe 3+ ( Table 1).…”
Section: Acid Solubilization Of Iron and Buffering Capacity Of Coalsmentioning
confidence: 98%